All our beautiful goodbyes : a novel - MacLean, Julianne (Lake Union Publishing, 2025)
"Like the untamed island around her, she weathers each storm to face a new tomorrow. 1946: World War II is over, and Emma Clarkson is poised to take flight. With dreams of attending university, she's ready to leave behind the wild beauty of Sable Island, the only home she's ever known. But when a handsome British sea captain is rescued from a nearby shipwreck, her destiny is forever changed. Emma falls deeply in love with Oliver Harris, but their romance is not meant to be. Oliver returns to the sea, while Emma vows to forget him and pursue her own ambitions. When a handsome veterinarian arrives on the island to study the wild horses, Emma finds love again, but soon discovers that all is not as it seems... 1995: Mourning the death of her beloved grandmother, Joanna Griffin is shocked to learn that her grandfather once loved a young woman named Emma, but lies, betrayals, and catastrophic events separated them forever. As Joanna crosses an ocean to solve the secrets of her grandfather's past, she learns that love is a powerful force, even mightier than the passage of time... A shining thread of hope illuminates this epic tale of lost love and fallen dreams, set in the remote splendor of Nova Scotia and spanning decades.